Biomechanical evaluation of percutaneous compression plate and femoral neck system in Pauwels type III femoral neck fractures - Xiaoping Xie; Songqi Bi; Qingxu Song; Qiong Zhang; Zhixing Yan; Xiaoyang Zhou; Tiecheng Yu (Journal of Orthopaedics and Traumatology, 2024)
Abstract Background The optimal treatment for Pauwels type III femoral neck fractures remains contentious. We aim to compare the biomechanical properties of three inverted cannulated compression screw (ICCS), femoral neck system (FNS), and percutaneous compression plate (PCCP) to determine which offers superior stability for unstable femoral neck fractures. Materials and methods Finite element analysis and artificial bone models were used to establish Pauwels III femoral neck fracture models. They were divided into ICCS, FNS, and PCCP groups based on respective internal fixation assemblies. The models were subjected to vertical axial loads (2100 N) and torsional forces (10 N × mm) along the femoral neck axis in the finite element analysis. The primary outcomes such as the Z axis fragmentary displacements, as well as displacements and the von Mises stress (VMS) distributions of internal fixations, were analyzed. Additionally, the artificial bones were subjected to progressively increasing vertical axial pressures and torsional moments at angles of 2°, 4°, and 6°, respectively. The vertical displacements of femoral heads and the required torque values were recorded. Results Finite element analysis revealed that under single-leg stance loading, the maximum Z-axis fragmentary displacements were 5.060 mm for ICCS, 4.028 mm for FNS, and 2.796 mm for PCCP. The maximum displacements of internal fixations were 4.545 mm for ICCS, 3.047 mm for FNS, and 2.559 mm for PCCP. Peak VMS values were 512.21 MPa for ICCS, 242.86 MPa for FNS, and 413.85 MPa for PCCP. Under increasing vertical loads applied to the artificial bones, the average vertical axial stiffness for the ICCS, FNS, and PCCP groups were 244.86 ± 2.84 N/mm, 415.03 ± 27.10 N/mm, and 529.98 ± 23.08 N/mm. For the torsional moment tests, the PCCP group demonstrated significantly higher torque values at 2°, 4°, and 6° compared with FNS and ICCS, with no significant difference between FNS and ICCS (P > 0.05). Conclusions Finite element analysis and artificial bone models indicated that PCCP offers the best compressive and rotational stability for fixing Pauwels type III femoral neck fractures, followed by FNS and then ICCS. No significant difference in rotational resistance was observed between FNS and ICCS in synthetic bones. Level of Evidence Level 5.